Rural middlemen : network of patronage - Srivastava, H. C. 1932-; Chaturvedi, Manjeet Kumar (New Delhi : Ashish Pub. House, 1986)
With reference to India.
Includes bibliographical references and index.
Ashik
Keywords: Rural development -- India; Businesspeople -- India